A Study of Depression Amongst Adolescent Students (Indian Journal of Psychology & Education, 2015)
The present study was designed to assess the percentage of depression in adolescent students. A sample of 300 adolescent students of 10th, 11th and 12th standard from government and public schools of Bhiwani and Rohtak district of Haryana state were administered Adolescent Depression Scale by Reynolds, (1998). Data were analyzed by Mean, Standard Deviation and percentage. The results found that the 12% adolescent students ware in high level, 33.67% moderate level and 54.33% low level of depression. Implications of the study for parents, teachers, counselors and researchers to understand to psychodynamic of adolescent students.